2013
DOI: 10.1177/0093650213490722
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Audio Message Complexity as Available Processing Resources

Abstract: This article describes and validates a human-centric measure of audio message complexity. Messages are coded in terms of the level of cognitive resources that would be automatically elicited and required to process the message. Indicators of automatic resources elicited come from counting the orienting eliciting audio content changes in radio messages (Acc). The indicator of resources required comes from counting the dimensions of audio information introduced (Aii) by these content changes. The combination pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The authors' initial study (Lang et al, 2015) showed faster response latencies for probes with high Acc. The best recognition results were achieved when Acc was high but Aii was low.…”
Section: Theoretical Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors' initial study (Lang et al, 2015) showed faster response latencies for probes with high Acc. The best recognition results were achieved when Acc was high but Aii was low.…”
Section: Theoretical Implicationsmentioning
confidence: 98%
“…However, the LC4MP provides substantial findings in regard to the specifics of audio information. A closer investigation on attention-related auditory complexity is linked with research on audio message complexity as available processing resource (Potter, Lang, & Bolls, 2008;Lang et al, 2015;Potter, Lynch, & Kraus, 2015;Potter & Lang, 2018).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…When the level of available resources is high, the message is thoroughly processed because far more resources are allocated to processing the message than required. On the contrary, when the available resources are low, the message is less thoroughly processed and task performance would decrease (Lang et al, 2013;Lang et al, 2006). The number of available resources an individual requires to process a message depends on the two conditions of stimuli: structural or formal complexity and information density.…”
Section: Influence Of Speech Rate and Information Density On Recognitmentioning
confidence: 99%
“…For example, message complexity is usually defined in terms of things about messages (e.g., redundancy, pacing, emotional content, syntax, content difficulty). DHCCST reconceptualizes message complexity as the moment‐to‐moment change in the human's level of automatically allocated and automatically required cognitive resources when interacting with a given message (Lang, Gao, Potter, Lee, Park, & Bailey, ; Lang, Kurita, Gao, Rubenking, ; Lee & Lang, in press). Various aspects of content are redefined in terms of their effect on automatic resource allocation and automatic resource requirements.…”
mentioning
confidence: 99%